Polska powieść polityczna u progu XXI wieku. O prozie Bronisława Wildsteina - Kania, Kamila (Tematy i Konteksty, 2015)
The demand that the public sphere, including culture, should be depoliticized after the transformations which took place in 1989 has proved to be baseless. Polish writers were challenged with the task of describing the events from Polish history and the political, social, cultural and economic changes that were taking place. Literature made an attempt to review the previous system and this issue seemed to be interesting for writers with both conservative and leftist views. One of the authors who delve into this kind of political novel is Bronisław Wildstein, whose artistic work has been imbued with political disputes in which he speaks out forcefully. It is not a cliché to call the novels of this writer and columnist fictionalized political manifestos. Wildstein unwaveringly raises the issues of history and politics as the things which determine our lives. Simultaneously, he refers to the tradition of prose analyzing the responsibility for public events. The writer tries to critically review the Polish People’s Republic (PRL) and its myths (including the Solidarity myth). Moreover, among the subjects frequently discussed one may find media policy and the world of politics from the inside.